2003
DOI: 10.1590/s0037-86822003000400006
|View full text |Cite
|
Sign up to set email alerts
|

Eventos adversos após vacinação contra influenza em idosos, Distrito de Campinas, SP, 2000

Abstract: Adverse reactions associated with vaccines are poorly documented in Brazil. The aim of this article was to identify the incidence of adverse effects to the influenza vaccine in the elderly of Campinas district, SP. A questionnaire was applied to a random systematic sample of people over 60 years of age (n = 206), participating in the Brazilian Vaccination Campaign during 2000. Temporal link was taken into account for general and local symptoms after vaccine. One or more symptoms were reported by 20.48% (CI 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
(3 reference statements)
4
5
0
14
Order By: Relevance
“…However, the prevalence of adverse events in the current study is consistent with the scientific literature as a whole, which also shows low prevalence of such events 23,28,31,32,33 . One Brazilian study identified pain at the vaccination site as the most frequent event (12.6%), followed by flu-like symptoms (7.8%).…”
Section: Reason N %supporting
confidence: 91%
See 1 more Smart Citation
“…However, the prevalence of adverse events in the current study is consistent with the scientific literature as a whole, which also shows low prevalence of such events 23,28,31,32,33 . One Brazilian study identified pain at the vaccination site as the most frequent event (12.6%), followed by flu-like symptoms (7.8%).…”
Section: Reason N %supporting
confidence: 91%
“…One Brazilian study identified pain at the vaccination site as the most frequent event (12.6%), followed by flu-like symptoms (7.8%). However, in the current study the subjects were asked (with a closed question) whether they had experienced any symptoms like fever, pain at the vaccination site, and others 31 . Lack of reports of pain in this study may have occurred due to difficulty by the elderly in recalling the symptom, or because neither the elderly nor the mass media appeared to consider it important.…”
Section: Reason N %mentioning
confidence: 99%
“…A higher percentage of female elderly (71.3%) was observed in the present study, similar to what was found by some authors (6,15) . In terms of the mean age of the participants, it was 70.30 years (standard deviation of +-7.62), which agrees with another study on the theme (6) .…”
Section: Discussionsupporting
confidence: 93%
“…The population studied has some similar characteristics to the population of other studies on the theme, regarding gender, age and vaccination status (4,6,13,14,15,16,17) . A higher percentage of female elderly (71.3%) was observed in the present study, similar to what was found by some authors (6,15) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation